Pengaruh Belajar Dari Rumah (BDR) Pada Masa Pandemim Terhadap Kreativitas Siswa Tema II Subtema II Di Kelas IV MI Nurul Hikmah Dlanggu - Ahmad Fajar; Fahrurrozi Fahrurrozi (LP3M IAI Al Urwatul Wutsqo Jombang, 2022)
Through the observations of the fourth grade researcher at MI Nurul Hikmah Dlanggu and interviews with the principal and principal, the researcher saw that the students were still less creative. The lack of student creativity is manifested in several aspects, namely students tend to be passive (rarely ask questions and express opinions), students only get information from what the teacher teaches, students lack the courage to develop their potential, and students are often asked to find problems. Difficulty when using alternative solutions. Learning From Home (BDR) is one of the lessons used by teachers during the pandemic. By doing learning through this BDR, teachers can deliver learning materials online (online). This study aims to determine the effect of learning from home (BDR) during the pandemic on the creativity of students in theme II sub-theme II in class IV MI Nurul Hikmah Dlanggu. The research design used is One Group Postes. The population of this study consisted of 55 students in class I, II, III, IV and 10 students in class IV as samples. The results of data analysis using the paired sample t-test of 0.000398, which means 0.000398 is smaller than 0.05, which means that there is an effect of learning from home on the creativity of fourth grade students of MI Nurul Hikmah Dlanggu.